2016
DOI: 10.18632/oncotarget.11979
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of human metapneumovirus (HMPV) infection by the innate sensing gene CEACAM1

Abstract: The innate sensing system is equipped with PRRs specialized in recognizing molecular structures (PAMPs) of various pathogens. This leads to the induction of anti-viral genes and inhibition of virus growth. Human Metapneumovirus (HMPV) is a major respiratory virus that causes an upper and lower respiratory tract infection in children. In this study we show that upon HMPV infection, the innate sensing system detects the viral RNA through the RIG-I sensor leading to induction of CEACAM1 expression. We further sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Similarly, PERK is activated upon endoplasmic reticulum stress, which might be expected during a viral infection, but not following treatment with IFN alone. Previous reports have shown that carcinoembryonic Ag-related cell adhesion molecule 1 (CEACAM1) has antiviral activity against human CMV, influenza virus, and metapneumovirus by suppressing mTOR-mediated protein synthesis (33,34). The membrane protein CEACAM1 is induced by innate sensors such as TLR-4 (35) and IFI16 (34) and delivers inhibitory signals via SHP1 (hematopoietic cells) or SHP2 (epithelial and endothelial cells) phosphatase activity through CEACAM1 ITIMs (36).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PERK is activated upon endoplasmic reticulum stress, which might be expected during a viral infection, but not following treatment with IFN alone. Previous reports have shown that carcinoembryonic Ag-related cell adhesion molecule 1 (CEACAM1) has antiviral activity against human CMV, influenza virus, and metapneumovirus by suppressing mTOR-mediated protein synthesis (33,34). The membrane protein CEACAM1 is induced by innate sensors such as TLR-4 (35) and IFI16 (34) and delivers inhibitory signals via SHP1 (hematopoietic cells) or SHP2 (epithelial and endothelial cells) phosphatase activity through CEACAM1 ITIMs (36).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PERK is activated upon endoplasmic reticulum stress which might be expected during a viral infection, but not following treatment with IFN alone. Previous reports have shown that carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) has antiviral activity against human cytomegalovirus, influenza virus and metapneumovirus by supressing mTOR-mediated protein synthesis (29, 30). The membrane protein CEACAM1 is induced by innate sensors such as TLR-4 (31) and IFI16 (30) and delivers inhibitory signals via SHP1 (haematopoietic cells) or SHP2 (epithelial and endothelial cells) phosphatase activity through CEACAM1 immunoreceptor tyrosine-based inhibitory motifs (ITIMs) (32).…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are known mostly for their role in controlling viral infections (20,21) and have been shown to be involved in cytomegalovirus (CMV) (22)(23)(24), influenza virus (6,(25)(26)(27)(28), Newcastle disease virus (29), vaccinia virus (30), and human metapneumovirus (HMPV) infections (31,32). NK cells express a large repertoire of inhibitory receptors, which mostly recognize major histocompatibility complex class I (MHC-I) molecules (missing self hypothesis [33]).…”
mentioning
confidence: 99%